2006 IEEE International Conference on Fuzzy Systems 2006
DOI: 10.1109/fuzzy.2006.1681814
|View full text |Cite
|
Sign up to set email alerts
|

Regularized Discriminant in the Setting of Fuzzy c-Means Classifier

Abstract: A fuzzy c-means classifier derived from a viewpoint of iteratively reweighted least square techniques (IRLS-FCM) has been proposed, in which membership functions are variously chosen and parameterized. This paper focuses on the postsupervised classifier design and three kinds of regularization methods for classification are addressed: 1) the exponent of membership function or weights in entropy term in the FCM clustering, 2) the modification of covariance matrices in defining Mahalanobis distances and 3) the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…For Breast cancer data, Euclidean distance, (i.e., p=0, c=3), was used and the classification decision was made by the maximum of cluster membership values in [8]. The result for this case by RFCMC was 2.79 ± 0.07, which is slightly better than the result in Table II in which Mahalanobis distances are used (p = 1) and the decision was made by the sum of memberships.…”
Section: Numerical Experimentsmentioning
confidence: 98%
See 3 more Smart Citations
“…For Breast cancer data, Euclidean distance, (i.e., p=0, c=3), was used and the classification decision was made by the maximum of cluster membership values in [8]. The result for this case by RFCMC was 2.79 ± 0.07, which is slightly better than the result in Table II in which Mahalanobis distances are used (p = 1) and the decision was made by the sum of memberships.…”
Section: Numerical Experimentsmentioning
confidence: 98%
“…The parameters of RFCMC are optimized by trial and error using 10-CV with a default partition and evaluated by 10 separate runs of 10-CV with random partitions. The results of FCMC on object data and optimized by trial and error are reported in [8].…”
Section: Numerical Experimentsmentioning
confidence: 99%
See 2 more Smart Citations
“…The classifier based on the GMM clustering is called a neural network [5] or the Gaussian mixture classifier (GMC). The classifier based on the FCM clustering is called the fuzzy c-means classifier (FCMC) [6], [7], [8]. For the detail derivation of the algorithm and the classification performance, see [9](WCCI'08).…”
Section: Introductionmentioning
confidence: 99%